Peran Copywriter dalam Pembuatan Iklan Layanan Masyarakat ”Stop Penyiksaan Hewan sebagai Sarana Hiburan” - Fabil Fauzi (STIKes Ibnu Sina Ajibarang, 2024)
There are 5,480 contents of animals torture spread across the world, and 1,626 of these contents come from Indonesia. This figure indicates that the content of torture in Indonesia has occurred so much and massively. The creator made a public service advertisement entitled ”Stop Penyiksaan Hewan Sebagai Sarana Hiburan”. The purpose of writing is to explain to the reader or audience how important it is to prepare a concept for making a public service advertisement. In this advertisement, the creator of the work acts as a copywriter. There are several stages in the creation of this work, namely pre-production, production and post-production. The copywriter's job is to create scripts, concepts and also create creative work plans. The creation of the script must follow the concept that has been made previously by the creator of the work and the art director. The creator of the work also helps in the production stage, such as taking footage and conducting interviews. In the post-production stage, the copywriter also helps with editing and also fills in voice over. The creator's hope is that the public service advertisement entitled ”Stop Penyiksaan Hewan Sebagai Sarana Hiburan” can educate the audience to understand how important it is to prepare the concept of a public service advertisement. The conclusion of this research is that a copywriter must be able to create a manuscript according to a previously created concept with limited time and the copywriter also needs to do target audience research.